Los beneficios tributarios como mecanismos para incentivar la donación de alimentos en supermercados en el área metropolitana de Lima, Perú (2018)
In Peru, until the beginning of 2016, foods with upcoming expiration dates, even though in good condition, did not go on sale to the public, nor donated to entities such as food banks, this because both operations were considered by the Peruvian Income Tax Law as sales in a strict sense, that is, in the light of Peruvian law they are taxed operations. In this sense, in order to recover some of the expenditure incurred in the purchase of such food, the companies had to destroy food, a measure opposed to rational economic logic, as well as compliance with the Sustainable Development Goals (SDG). At the end of 2016, a tax reform was approved, which included the creation of a tax deduction for food donation. This paper analyzes the effects of said norm, taking as a reference the Colombian proposal contained in the so-called “Anti-food Waste Law to Fight Hunger in Colombia”. The objective of this paper is to determine if the tax benefits of the Peruvian regulations function effectively as an incentive mechanism for food donation in supermarkets located in the Metropolitan Area of Lima. The present research work uses a qualitative and quantitative approach, of descriptive - explanatory type from the comparison of normative frameworks, with which it is sought to clarify the fiscal and parafiscal scope of the indicated tax norm in Peru and its impact in pro of social development and the effects it has as a social responsibility measure.